Sound radiation from a cylindrical shell with a multilayered resonant coating. (15th October 2022) - Lin, Cikai; Sharma, Gyani Shankar; Eggler, Daniel; Maxit, Laurent; Skvortsov, Alex; MacGillivray, Ian; Kessissoglou, Nicole
Highlights: Designs of multilayered coatings embedded with resonant inclusions are presented. The influence of frequency tuning local resonances of the inclusions is examined. A coating with voids effectively decouples a shell from the surrounding water. Broadband reduction of radiated sound from a multilayered coated shell is achieved. Mechanisms governing acoustic performance of the coating designs are described. Abstract: The vibroacoustic response of a structurally excited cylindrical shell submerged in water is presented. The shell is coated with a soft elastic material embedded with circumferential arrays of resonant inclusions. The coating is modelled as a multilayered equivalent fluid composed of homogeneous layers of the host soft material and homogenised layers comprising voids or hard inclusions. The radiated acoustic pressure is analytically derived by assembling and solving continuity and kinematic conditions at the interfaces between the cylindrical shell and the multilayered coating. Coating designs with different combinations of homogenised layers are examined. Physical mechanisms governing acoustic performance of the various coating designs are described. We show that the material of the inclusions, tuning the local resonances of the inclusions and the distribution of the homogenised layers within the coating have a significant effect on the shell vibroacoustic response. Graphical abstract: Image, graphical abstract